2019
DOI: 10.3390/su11164348
|View full text |Cite
|
Sign up to set email alerts
|

“Seeing” or “Being Seen”: Research on the Sight Line Design in the Lion Grove Based on Visitor Temporal–Spatial Distribution and Space Syntax

Abstract: Research on the sight line design of the Classical Chinese Garden (CCG) is an important issue of CCGs' sustainable development. Taking the Lion Grove as a case, GPS data loggers and questionnaires were employed to collect visitor temporal-spatial data and visiting motivations. We then calculated the "Revisiting Proportion" and "Average Speed" values. Furthermore, we selected the "Visual Control" values analyzed by Depthmap as an indicator of visibility. The statistical analysis of the relationship among "Revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The visual graph analysis, built on the logic of isovist analysis [24] by default applied on an at-eye level to estimate what people can see, can also be used on an at-knee level to investigate where people can move [25]. Moreover, studies on pedestrian walking behaviour [26] showed that the visibility of specific spaces impacts pedestrian wayfinding choices and triggers intentional visual design practice [27]. Similar relationships were established for mixed land use [28].…”
Section: The Growing Interest In Space Syntax Application Into Walkab...mentioning
confidence: 91%
“…The visual graph analysis, built on the logic of isovist analysis [24] by default applied on an at-eye level to estimate what people can see, can also be used on an at-knee level to investigate where people can move [25]. Moreover, studies on pedestrian walking behaviour [26] showed that the visibility of specific spaces impacts pedestrian wayfinding choices and triggers intentional visual design practice [27]. Similar relationships were established for mixed land use [28].…”
Section: The Growing Interest In Space Syntax Application Into Walkab...mentioning
confidence: 91%
“…The main building within the garden, Haitangchunwu (Table 5; Route 1, 33-34; Route 2, 13-14; Route 3, 41-42; Route 4, 40-41), represents the courtyard with the highest values for the IA, IO, IDM, and IMR parameters within the Loquat Garden. 3, Table 5; Route 1, 30-34; Route 2, 7-14; Route 3, 35-42, Route 4, [34][35][36][37][38][39][40][41] Table 5 shows that the four visual parameters of the Loquat Garden Area (C), except for the waist-shaped entrance gate, are generally the lowest throughout the entire garden. The low parameters are due to the sub-garden being a tranquil 'gardens within a garden' enclosed by walls.…”
Section: Comparison Of the Analysis Of Four Routes In The Centralmentioning
confidence: 99%
“…D. S. Tceluiko et al analyzed garden development's history and spatial structure using spatial syntax theory [33,34]. Tiantian Zhang et al combined field surveys with visibility analysis to analyze the visual line design of Lion Grove Garden [35]. Rongrong Yu et al published several articles using spatial syntax to study traditional Chinese private gardens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there needs to be more research addressing the temporal-spatial narratives along garden paths. Rongrong Yu and others employed isovist analysis to study gardens' complex visual fields and path systems, extracting design elements to create new garden architecture [51][52][53]. Nevertheless, their research needed to be integrated with narrative theory.…”
Section: Introductionmentioning
confidence: 99%